Thoracic Endovascular Aortic Repair for Blunt Thoracic Aortic Injury: A Report of Three Cases in Which Surgeries Were Performed at Different Timings - Yohei Kawatani; Hirotsugu Kurobe; Yoshitsugu Nakamura; Yuji Suda; Takaki Hori (Case Reports in Surgery)
Introduction. Blunt thoracic aortic injury (BTAI) is a critical condition. Thoracic endovascular aortic repair (TEVAR) is considered a surgical treatment for BTAI. Reports reveal that some patients benefit from conservative and delayed operation rather than emergency operative therapy. Here, we present three BTAI cases that were treated with TEVAR using different timings. Case Presentation. Case 1 involved a 49-year-old man injured in a car accident and who went into shock. After stabilization with Advanced Trauma Life Support in the emergency room, TEVAR was performed immediately. Case 2 involved a 69-year-old man who was injured after falling. His hemodynamic status was stable and enhanced computed tomography revealed intraluminal hematoma. He underwent TEVAR 15 days after the injury occurred, following conservative therapy. Case 3 involved a 60-year-old man who was injured in a car accident and presented BTAI with subarachnoid hemorrhage and diaphragm tear. A pseudoaneurysm was observed in the distal aortic arch. After open abdominal exploration, diaphragm repair, and observation for subarachnoid hemorrhage, TEVAR was performed 8 hours after arrival. All three patients survived. Conclusions. We treated BTAI successfully. We suggest that TEVAR is useful for BTAI. The timing of the operation and therapeutic option, including conservative therapy, should be decided for each patient.